Association of sarcopenia with functional decline in community‐dwelling elderly subjects in Japan. Issue 4 (3rd March 2013) - Tanimoto, Yoshimi; Watanabe, Misuzu; Sun, Wei; Tanimoto, Keiji; Shishikura, Kanako; Sugiura, Yumiko; Kusabiraki, Toshiyuki; Kono, Koichi
<x xml:space="preserve">Abstract</x> Aim The present study aimed to determine the association of sarcopenia, defined by muscle mass, muscle strength and physical performance, with functional disability from a 2‐year cohort study of community‐dwelling elderly Japanese people. Method Participants were 743 community‐dwelling elderly Japanese people aged 65 years or older. We used bioelectrical impedance analysis (BIA) to measure muscle mass, grip strength to measure muscle strength, and usual walking speed to measure physical performance in a baseline study. Functional disability was defined using an activities of daily living (ADL) scale and instrumental activities of daily living (IADL) scale at baseline and during follow‐up examinations 2 years later. Logistic regression analysis, adjusted for age and body mass index, was used to examine the association between sarcopenia and the occurrence of functional disability. Results In the present study, 7.8% of men and 10.2% of women were classified as having sarcopenia. Among sarcopenia patients in the baseline study, 36.8% of men and 18.8% of women became dependent in ADL at 2‐year follow up. From the logistic regression analysis adjusted by age and body mass index, sarcopenia was significantly associated with the occurrences of physical disability compared with normal subjects in both men and women. Conclusions Sarcopenia, defined by muscle mass, muscle strength and physical performance, was associated with functional decline over a 2‐year period in elderly Japanese. Interventions to prevent sarcopenia are very important to prevent functional decline among elderly individuals. Geriatr Gerontol Int 2013; 13: 958–963.